2016
DOI: 10.1007/s12144-016-9470-y
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Family-to-Work Conflict and Work-Family Balance in the Relationship between Family Support and Family Satisfaction: A Three Path Mediation Approach

Abstract: The purpose of this study is to test the serial mediation effect of family-to-work conflict and work-family balance in the relationship between family support and family satisfaction. Using a survey-based methodology and an online questionnaire, responses were obtained from 288 faculty members who work in higher education institutions in cities from the southern part of India. Partial least square structural equation modeling and PROCESS macros were used to test the proposed hypotheses of the three path mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 65 publications
2
26
0
1
Order By: Relevance
“…An inability to balance work and family domain duties runs the risk of being detrimental to even the most accomplished employee [ 24 ]. To our knowledge, few studies [ 26 ] have attempted to understand the mediating role of work-family balance. Studies are even scarcer on the bearing of work-family conflict on work-family balance.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…An inability to balance work and family domain duties runs the risk of being detrimental to even the most accomplished employee [ 24 ]. To our knowledge, few studies [ 26 ] have attempted to understand the mediating role of work-family balance. Studies are even scarcer on the bearing of work-family conflict on work-family balance.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Studies performed in different countries have reported that family support is related to higher levels of subjective well-being and life satisfaction [ 7 , 21 , 22 , 23 , 24 , 25 , 26 ], more satisfaction with food-related life [ 12 , 27 , 28 , 29 ] and greater satisfaction with family life [ 16 , 30 , 31 ] in adolescents and youth.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…In fact, the level of balance between work and family impacts other life domains and is likely to affect not only the individual parent but also those closest to them [ 33 , 37 ], such as the couple and their children [ 35 ]. However, while the impact of the family-work relationship has been extensively studied in couples for example [ 31 , 35 , 37 , 38 , 39 , 40 ], there remain few studies that have assessed the influence of the parental balance between work and family on their children’s well-being [ 5 , 33 , 41 , 42 ]. Strazdins et al [ 43 ] found that unconventional work schedules contributed to depressive symptoms in parents, which negatively affected the well-being of their children.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Mikkelsen and Burke (2004) examined 766 male and female Norwegian POs and found that work-family conflict was related to psychological health, while Zavala and Kurtz (2016) found that POs that received family support were less likely to adopt maladaptive coping strategies, such as alcohol consumption. Thus, both work-family conflict and family support variables must be considered to better understand the role of families in work-related stress (Pattusamy and Jacob, 2017). Thompson et al (2005) found that in POs, support from supervisors was related to a decrease in stress.…”
Section: Sts and The Job Demands-resources Modelmentioning
confidence: 99%